Luminous quasars do not live in the most overdense regions of galaxies at z ∼ 4. (7th December 2017) - Uchiyama, Hisakazu; Toshikawa, Jun; Kashikawa, Nobunari; Overzier, Roderik; Chiang, Yi-Kuan; Marinello, Murilo; Tanaka, Masayuki; Niino, Yuu; Ishikawa, Shogo; Onoue, Masafusa; Ichikawa, Kohei; Akiyama, Masayuki; et al.
Abstract: We present the cross-correlation between 151 luminous quasars ( M UV  < −26) and 179 protocluster candidates at z  ∼ 3.8, extracted from the Wide imaging survey (∼121 deg 2 ) performed as part of the Hyper Suprime-Cam Subaru Strategic Program (HSC-SSP). We find that only two out of 151 quasars reside in regions that are more overdense compared to the average field at >4 σ. The distributions of the distances between quasars and the nearest protoclusters and the significance of the overdensity at the positions of quasars are statistically identical to those found for g -dropout galaxies, suggesting that quasars tend to reside in almost the same environment as star-forming galaxies at this redshift. Using stacking analysis, we find that the average density of g -dropout galaxies around quasars is slightly higher than that around g -dropout galaxies on 1.0–2.5 pMpc scales, while at <0.5 pMpc that around quasars tends to be lower. We also find that quasars with higher UV luminosity or with more massive black holes tend to avoid the most overdense regions, and that the quasar near-zone sizes are anti-correlated with overdensity. These findings are consistent with a scenario in which luminous quasars at z  ∼ 4 reside in structures that are less massive than those expected for the progenitors of today's rich clusters of galaxies, and possibly that luminous quasars may be suppressing star formation in their close vicinity.